Effectivity and compatibility of Azotobacter and Bacillus for biological control agents of fusarium wilt on banana seedlings. (March 2019) - Proboningrum, A; Hadiwiyono,; Widono, S; Sholahuddin,
Abstract: Fusarium wilt, caused by Fusarium oxysporum f.sp. cubense (Foc), is important banana. This disease infect in any growing and generation stages resulted in banana harvesting failure. For that, effective method to control its spreading need to be developed. Rhizospheric and endophytic bacteria belongs to biological control agent (BCA) which could be effective to control Foc disease. These BCAs are able to produce enzymes and toxics which are negatively impact to pathogen growth, in the other side these compounds are able to promote plant growth. Based on that, this research was aimed to know the effectivity and compatibility of using Azotobacter A01 isolate, Bacillus B01 isolate (rhizospheric) and Bacillus B16 isolate (endophytic) as BCAs for banana wilt. In this study, banana seedlings were produced using tissue culture method, acclimated for 2 months then infested by BCA at 10 8 cfu g −1 on day 7 before Foc inoculation at 10 6 conidia g −1 of medium. The wilt disease and seedlings growth assessment were conducted weekly for 56 days period. As the result, all BCAs isolate in single or combination, were effective to control fusarium wilt by decrease its intensity. Moreover, isolate combination shows more compatible and effective as BCA in control the disease.